Preliminary psychometric investigation of Serbian Mindful Attention and Awareness scale (MAAS) and potential role of Mindful Attention and Awareness in behavioral regulation among students (Engrami, 2022)
Introduction: Recent studies about Mindful Attention and Awareness elucidated its potential role in affective difficulties and behavioral regulation, but authors call for further investigation of potential underlying mechanisms.Research goal: The current study was conducted in order to examine the preliminary psychometric properties of the Serbian Mindful Attention and Awareness scale, its relationship with positive psychological constructs, along with its mediating role in the relationships of Depressiveness as a trait, with behavioral Activation, and Avoidance.Method: A cross-sectional research was conducted on a sample of 504 students of different levels and courses of education in the Serbian speaking area.Results: Serbian version of Mindful Attention and Awareness scale demonstrated high reliability (α=0.83) and a single factor solution that was found to be the most adequate. Significant correlations with theoretically related positive psychological constructs such as Gratitude (r=0.12, p
Keywords: Mindful Attention and Awareness; Depressiveness; Behavioral activation; Avoidance